A simplified model for analysis of high‐rise buildings equipped with hysteresis damped outriggers. (6th September 2013) - Deng, Kailai; Pan, Peng; Lam, Alexandre; Xue, Yantao
SUMMARY A simplified model is developed to estimate the seismic response of high‐rise buildings equipped with hysteresis damped outriggers. In the simplified model, the core tube is considered as a cantilever beam, and the effects of outriggers on the core tube are considered as concentrated moments. Modal decomposition method is adopted to obtain the seismic response of the simplified model. To investigate the accuracy and effectiveness of the simplified model, a high‐rise building with a height of 160 m was adopted as the example structure, and its response subjected to a ground motion was analyzed using the simplified model. A corresponding finite element model was built and analyzed by a finite element program called SAP2000 (Computers and Structures, Inc. Berkeley, California, United States). The analysis results obtained from the two models were compared. To consider the randomness of the ground motion, comparisons between the two models were further conducted using another 22 ground motions. It is found that the analysis results obtained from the simplified model agree well with those obtained from the finite element model, and the computation time used for the simplified model is almost negligible compared to that used for the finite element model. Such observations demonstrate that the simplified model is accurate and effective. Copyright © 2013 John Wiley & Sons, Ltd.